Reprogramming of CaCo2 colorectal cancer cells after using the complex of poly-(N-vinylpyrrolidone) with small non-coding RNAs - Klimenko, Oxana V; Shtilman, Mikhail (Toxicology reports, 2019)
Small non-coding RNAs control normal development and differentiation in the embryo. These regulatory molecules play a key role in the development of human diseases and are used often today for researching new treatments for different pathologies. In this study, CaCo2 colorectal adenocarcinoma cells were initially epigenetically reprogrammed and transformed into CD4+ cells with nano-sized complexes of amphiphilic poly-(N-vinylpyrrolidone) (PVP) with miRNA-152 and piRNA-30074. The transformation of cells was confirmed by morphological and genetic changes in the dynamic of reprogramming. CD4+ lymphocytes marker was detected using immunofluorescence. Amphiphilic poly-(N-vinylpyrrolidone)/small non-coding RNAs complexes were investigated for transfection efficiency and duration of transfection of CaCo2 colorectal adenocarcinoma cells using fluorescence.
Keywords: AGO2, argonaute 2; Reprogramming; PIWIL1, piwi-like protein 1; CaCo2 colorectal adenocarcinoma; mTOR, mechanistic target of rapamycin; TSS, transcriptional start sites; HOXA10, homebox A10; Wnt-1, wingless type MMTV integration site family, member 1; FGF2, fibroblast growth factor 2; GITR3A, glucocorticoid-induced TNFR-related protein; KIR1DL2, CD158b, expressed on natural killer cells and a subset of T cells; miRNA-152; RB1, retinoblastoma 1; CD, cluster of differentiation; miR, micro-RNA; DTT, dithyothreitol; HMOX1, heme oxygenase 1; piRNA-30074; TNFRS6B, TNF receptor superfamily 6B; IL, interleukin; OCT4, octamer-binding transcription factor 4; H3K9me3, tri-methyl lysine 9 of histone H3; PNVP, poly-(N-vinylpyrrolidone); VMAF, musculoaponeurotic fibrosarcoma; BACH1, BTB domain and CNC homolog 1; TE, transposon elements; SncRNAs, small non-coding RNAs; ERK1/2, extracellular signal regulated kinase ½; HILI, human piwi; DICER1, ribonuclease III; piR, piwi-interacting RNA, P-element induced wimpy testis interacting RNA; iPS, induced pluripotent stem cells; Amphiphilic poly-(N-vinylpyrrolidone); Polymer carriers; MKI-67, marker of proliferation ki-67; ICOS1B, inducible T-cell co-stimulator; DNMT1, DNA methyltransferase 1; TGFBR2, transforming growth factor beta receptor 2